The Impact of Formative Assessment on Developing EFL Student-Teachers' Language Competences as Domain-Specific - Nikolovska, A., Bekar, M. & Trajkova Strezovska. Z. (My University, 2023)
The paper reports on the outcomes of research carried out at a North Macedonian public university aimed at developing the language competences of prospective EFL teachers through formative assessment. For the study’s purposes, a CEFR-based assessment tool was designed for teacher, peer and self-assessment of the ETP (English for-teaching purposes) competences of fourth year student-teachers (n=15) micro-teaching lower year students. Fluency, accuracy, interaction, stimulating the development of ideas, and addressing audiences were the formative assessment criteria used to check if there was progress from the first to the third micro-teaching session as a result of formative feedback and assessment training. Additionally, two surveys for student-teachers and peer assessors were used aimed at exploring: a) the effects of formative feedback on students’ language competences and teaching skills; b) the effects of formative assessment training on students’ peer- and self-assessment skills; and c) the professional and personal benefits of formative assessment training for students. Apart from many personal benefits from the project, findings revealed positive effects of formative assessment on students’ language competences and teaching skills; specifically on the awareness of the complexity of ETP competences and the skills for tackling various classroom, assessment and material design challenges.
Keywords: formative assessment, pre-service EFL teachers, language competences, English-for-teaching purposes, CEFR